Autopercepción del estado de salud familiar en un area metropolitana de Bucaramanga (2016)
Introduction: As transformable open system to change, and key structural element family company, develops and performs functions through subsystems formed by generation, gender, interest and function, according to the positive or negative influence, it is a risk factor that contributes or not to maintain the health and preservation of the quality of life of all its members. Objective: To evaluate the perception of the state of family health Methodology: Cross-sectional study in the metropolitan area of Bucaramanga from February to November 2014. Universe 120 families of which 70 participated voluntarily, said the head of the household questionnaire familiar self-rated health. The information was processed in the program SPSSS, reliability analysis, description of the results variables, calculating measures of central tendency and dispersion. Results: Nuclear family predominated 45.7 %, with 4 members 74.3 % 52.9 % female gender prevails between 18 and 44 years 45.2 %, basic primary education 52.9 %. 32.9 % reported hypertension, diabetes 14.3 % and 4.3 % dyslipidemia, neuropsychiatric 14.3 %. The self-rated general health was 39 points of 84 expected. Conclusions: In the studied population the familiar self-rated health is a risk to the health of the family, which requires actions to strengthen behaviors that strengthen the family atmosphere that is conducive space to promote healthy lifestyles at different stages life cycle of a person. © 2016, Editorial Ciencias Medicas. All rights reserved.